2020
DOI: 10.1049/iet-its.2019.0860
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of bus stop location and berth number on urban network traffic performance

Abstract: The effects of operational characteristics of the public transport system on the performance of the urban network traffic flow and the public transport system have been widely investigated at the local level. However, to the best of authors' knowledge there is no attempt to investigate these characteristics at the network level. This study bridges this gap through the notion of network macroscopic fundamental diagram (NMFD). In particular, the effects of the bus stop location (i.e. far-side and nearside) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In this context, Lammera, Abdulla, and other scholars conducted a study on the traffic network of German cities, specifically analyzing its complexity and small-world characteristics [ 37 , 38 ]. In addition, a research study investigating the correlation between street networks and traffic flow in the city center revealed that urban road traffic networks can be broadly classified into several types, such as square grid, belt, radial, circular radial, and free-form [ 39 , 40 ]. However, the physical road infrastructure is not limited to a single configuration, but often consists of a combination of two or more basic road networks [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Lammera, Abdulla, and other scholars conducted a study on the traffic network of German cities, specifically analyzing its complexity and small-world characteristics [ 37 , 38 ]. In addition, a research study investigating the correlation between street networks and traffic flow in the city center revealed that urban road traffic networks can be broadly classified into several types, such as square grid, belt, radial, circular radial, and free-form [ 39 , 40 ]. However, the physical road infrastructure is not limited to a single configuration, but often consists of a combination of two or more basic road networks [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Johari et al examined the impact of the performance of an urban public transport system on the performance of an urban transport network [14] macroscopically. The authors analyzed the impact of the bus route network on the speed of the traffic flow in 3 locations (near, far, middle), taking into account the intersections of bus stops in different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…At present, research focused on the traffic conditions in entrances and exits of the off-street parking is still very rare. Previous research mainly focuses on the complex impact of the bus stop [9][10][11][12][13][14] and on-street parking [15][16][17][18] on the traffic flow. Compared with other road facilities, the settings of entrances and exits of parking facilities can bring more complicated impact: on the one hand, due to the uncertainty of the occurrence and attraction of parking facilities, the temporal and spatial distribution of parked vehicles are more disorderly; the intermittently concentrated entering and departing of vehicles enhance the occasional disturbance to the road; on the other hand, the interwoven flow of incoming and outgoing vehicles, the traffic flow of the main road, and the flow of motor vehicles and nonmotorized vehicles [19] increase the heterogeneity of the traffic flow and the complexity of the occurrence of congestion in this area to a certain extent.…”
Section: Introductionmentioning
confidence: 99%